A Dynamic Bandwidth Allocation Algorithm Based on Differentiated Service Cycle in Multi-Service Hybrid VPON. Issue 5 (2nd November 2022) - Hui, Jianqiang; Gan, Chaoqin; Liu, Xuefeng; Zhan, Nianfei
ABSTRACT: In this paper, a dynamic bandwidth allocation (DBA) algorithm based on differentiated service cycle (DSC) in multiple service (multi-service) hybrid Virtual Passive Optical Network (VPON) is proposed. The DSC algorithm introduces neural network prediction and improves the polling mechanism between Optical Network Unit (ONU) and Optical Line Terminal (OLT). DSC can be applied to multi-service VPON scenarios. By introducing neural network, the problem that traditional prediction methods can only predict one polling cycle service traffic will be solved. By establishing the separation mechanism of report cycle and prediction cycle, the idle time in multi-wavelength VPON is eliminated, and the bandwidth consumption caused by a large number of REPORT messages is reduced. By proposing differentiated service cycle polling mechanism, the transmission delay of high priority service traffic caused by the simultaneous interpreting of multiple services in offline DBA algorithm can be reduced. Finally, by the simulation and analysis, the effectiveness of the proposed model is demonstrated.